2013
DOI: 10.1200/jco.2012.47.7901
|View full text |Cite
|
Sign up to set email alerts
|

International Myeloma Working Group Recommendations for the Treatment of Multiple Myeloma–Related Bone Disease

Abstract: Bisphosphonates (BPs) should be considered in all patients with MM receiving first-line antimyeloma therapy, regardless of presence of osteolytic bone lesions on conventional radiography. However, it is unknown if BPs offer any advantage in patients with no bone disease assessed by magnetic resonance imaging or positron emission tomography/computed tomography. Intravenous (IV) zoledronic acid (ZOL) or pamidronate (PAM) is recommended for preventing skeletal-related events in patients with MM. ZOL is preferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
298
0
10

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 317 publications
(311 citation statements)
references
References 86 publications
3
298
0
10
Order By: Relevance
“…4 In addition, some randomized trials have shown clinical benefits for bisphosphonates in these patients when they are administered during cytotoxic therapy. [8][9][10] These results and some preclinical studies argue in favor of an antimyeloma effect for the most potent bisphosphonates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In addition, some randomized trials have shown clinical benefits for bisphosphonates in these patients when they are administered during cytotoxic therapy. [8][9][10] These results and some preclinical studies argue in favor of an antimyeloma effect for the most potent bisphosphonates.…”
Section: Discussionmentioning
confidence: 99%
“…3 Intravenous bisphosphonates are indicated in patients with MM, with or without detectable osteolytic bone lesions on conventional radiography, who are receiving antimyeloma therapy as well as in patients with osteoporosis or osteopenia resulting from myeloma. 4 Although the main reason for their indication is that bisphosphonates prevent skeletal-related events, there are also controversial data suggesting that zoledronic acid (ZA) has an anti-myeloma effect. This hypothesized antitumor effect is based on findings in pre-clinical studies, [5][6][7] reproduced in small series of patients, 8 and subanalyses of clinical trials, 9,10 particularly, the large MRC-IX trial 9 conducted in newly diagnosed patients treated with either chemotherapy (CVAB) or thalidomide-based therapy (CTD), who were assigned to receive either ZA or clodronate.…”
Section: Introductionmentioning
confidence: 99%
“…69 At present, intravenous bisphosphonates are recommended for all MM patients requiring therapy, which should be continued with active disease and reassumed after disease relapse (1A). 70 It is important to note that denosumab, a monoclonal antibody to RANK-ligand approved for use in breast and prostate cancer metastatic to bone, is currently being tested in a large randomized trial against ZOL, because the smaller randomized trial in fewer than 200 MM patients of denosumab versus ZOL showed an inferior survival in the subset of MM patients treated with denosumab. 71 The currently available data, therefore, do not yet support the use of denosumab for the treatment of myeloma-related bone disease.…”
Section: Optimal Management Of Myeloma-related Bone Diseasementioning
confidence: 99%
“…They can be stopped after approximately 2 years of use, if there is full response or very good partial response. Re-administration of those drugs is recommended, if there is recurrence [18]. The vit D, calcium, phosphate, magnesium and albumin levels and the renal functions should be evaluated before bisphosphonate use in malignant disorders [19].…”
Section: Discussionmentioning
confidence: 99%